<h2>
<em>Answer:</em></h2><h2>
<em>5</em><em>2</em><em>.</em><em>7</em><em>8</em><em>5</em><em>6</em><em> </em><em>cm</em></h2>
<em>Solution</em><em>,</em>
<em>diameter</em><em>=</em><em>1</em><em>6</em><em>.</em><em>8</em><em> </em><em>cm</em>
<em>radius=</em><em>8</em><em>.</em><em>4</em><em> </em><em>cm</em>
<em>Circumference</em><em> of</em><em> </em><em>circle</em><em>=</em><em>2</em><em> </em><em>pi </em><em>r</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em> </em><em>2</em><em>*</em><em>3</em><em>.</em><em>1</em><em>4</em><em>2</em><em>*</em><em>8</em><em>.</em><em>4</em>
<em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em> </em><em>=</em><em>5</em><em>2</em><em>.</em><em>7</em><em>8</em><em>5</em><em>6</em><em> </em><em>cm</em>
<em>Hope </em><em>it</em><em> helps</em>
<em>Good </em><em>luck</em><em> on</em><em> your</em><em> assignment</em>
I think it's 1,876,480 but I'm not sure
This is a bit harder. I suggest getting the Domain and Range for the function of x.
If any of these answers have, an infinite domain and (3, infinite) range. That will be your answer.
Your answer is B.
f(x) = 2x²+3 has the same domain and range as x²+3
Answer:
....................
Step-by-step explanation:
Answer:
x = 3, y = 1 is the solution of the given system.
Step-by-step explanation:
Here, the given system of equations is:
y = -x + 4 ...... (1)
y = x - 2 .......... (2)
Now, to find the solution of the system, SUBSTITUTE the value of y from equation (1) in to the equation (2). We get ,
y = x - 2 ⇒ -x + 4 = x - 2 ( as from (1), y = -x + 4)
or, -x -x = -2 -4
or, - 2 x = -6 ⇒ x = 6/2 = 3
or, x = 3
⇒ y = x - 2 = 3 - 2 = 1
⇒ y = 1
Hence, x = 3, y = 1 is the solution of the given system.